The crucial role of immunoblots in distinguishing Lyme disease from tick-borne relapsing fever - Zahra Ali Haque; Muhammad Aqib Farooq Khan; Mahnoor Shahzad (Journal of Vector Borne Diseases)
Lyme disease (LD) and tick-bome relapsing fever (TBRF), both consequences of Borrelia burgdorferi infection, pose significant public health threats with overlapping symptomatic presentations. A previous study explores the potential of line immunoblots (IBs) as a transformative diagnostic tool for distinguishing between LD and TBRF. By employing strategically designed recombinant proteins on nitrocellulose membrane strips, IBs offer enhanced accuracy in identifying antibodies in patient samples. While serological assays for LD have seen advancements, the diagnostic landscape for TBRF lags behind, necessitating comprehensive diagnostic approaches capable of addressing both conditions. Immunoblots, with their ability to detect antibodies with exceptional precision, not only facilitate accurate diagnosis but also enable tailored patient treatment and monitoring of treatment response. The study underscores the importance of immunoblots in improving diagnostic accuracy and patient outcomes for tick- borne diseases. In conclusion, as research progresses in understanding LD and TBRF, immunoblots emerge not only as diagnostic tool but also as valuable resources for advancing research and refining patient treatment strategies.